Altered inorganic composition of enamel and dentin in mice teeth chronically exposed to an enriched mineral environment at Furnas, São Miguel (Azores) - Cunha, Luís (2011)
Active volcanic environments pose a multifactorial stress challenge to local organisms, including the domestic mouse Mus musculus. Energy-dispersive X-ray microanalysis was used to determine the elemental composition of lower incisor enamel and dentin from Mus musculus inhabiting the hydrothermal field at Furnas volcano in the Azores (Portugal). Elemental concentration for Ca, P, Na and Cl was found to be significantly different in mice from the volcanic site when compared to an unexposed group. Enamel surface was differently coloured; animals from the volcanic site showed a prominent yellow/red coloration when compared to the unexposed group, probably due to mineral deposition in the former group. These results are discussed in relation to the environment in which specimens were caught.